Upregulation of cathepsin L gene under mild cold conditions in young Japanese male adults - Yasukochi, Yoshiki; Shin, Sora; Wakabayashi, Hitoshi; Maeda, Takafumi (Journal of Physiological Anthropology, 2021)
Physiological thermoregulatory systems in humans have been a key factor for adaptation to local environments after their exodus from Africa, particularly, to cold environments outside Africa. Recent studies using high-throughput sequencing have identified various genes responsible for cold adaptation. However, the molecular mechanisms underlying initial thermoregulation in response to acute cold exposure remain unclear. Therefore, we investigated transcriptional profiles of six young Japanese male adults exposed to acute cold stress. In a climatic chamber, the air temperature was maintained at 28°C for 65 min and was then gradually decreased to 19°C for 70 min. Saliva samples were obtained from the subjects at 28°C before and after 19°C cold exposure and were used for RNA sequencing. In the cold exposure experiment, expression levels of 14 genes were significantly changed [false discovery rate (FDR) < 0.05] although the degree of transcriptional changes was not high due to experimental conditions or blunted transcriptional reaction in saliva to cold stress. As a result, differential gene expression analyses detected the cathepsin L (CTSL) gene to be significantly upregulated, with FDR < 0.05 and log fold change value > 1; thus, this gene was identified as a differentially expressed gene. Given that the cathepsin L protein is related to invasion of the novel coronavirus (SARS-CoV-2), mild cold stress might alter the susceptibility to coronavirus disease-19 in humans. The gene ontology enrichment analysis for 14 genes with FDR < 0.05 suggested that immune-related molecules could be activated by mild cold stress. The results obtained from this study indicate that CTSL expression levels can be altered by acute mild cold stress.